Distinct Patterns of Host Adherence by Neisseria gonorrhoeae Isolated from Experimental Gonorrhea. (15th May 2021) - He, Yingxia; Zhang, Song; Zhang, Yingmiao; Wu, Bicong; Xue, Ying; Ye, Chenglin; Li, Qiao; Olivia, Adhiambo Njiri; Tembo, John Mambwe; Chen, Hongxiang; Cai, Huahua; Chen, Tie
Abstract : Neisseria gonorrhoeae ( N. gonorrhoeae, gonococci, or GC), the etiologic agent of gonorrhea, is a human-obligate bacterial pathogen. The GC surface contains pili that mediate the adherence to host cells. Studies have shown that GC pili, coded by pilin genes, undergo remarkable changes during human experimental gonorrhea, possibly generated by DNA phase variation during infection. The question that arises is whether the changes in pilins can alter the adherence capacity of N. gonorrhoeae to host cells. In this study, six variants initially isolated from male volunteers infected with one single clone of GC were examined for their adherence patterns with human Chang conjunctiva cells. In this study, we showed that the variants showed distinct adherence patterns to this cell line under light microscopy and scanning electron microscopy. Moreover, two reisolates showed higher adherence capacities than that of the input strain. The results provide an additional example as to how the pilus variation may play a role in the pathogenesis of N. gonorrhoeae .